Statistics in road crashes with victims in Costa Rica for the period 2012-2016: An approach to the road safety analysis from the masculinity and femininity social roles - Pérez Stéfanov, Bohián (2025)
The road accidents in Costa Rica have taken the lives of more than 1897 people between 2012 and 2016, of whom 86% were men, the vast majority of car or motorcycle drivers. Of the remaining 14% of women who died, more than 75% were passengers in a vehicle, pedestrians or cyclists. These data raise a hypothesis: the road system and mobility in Costa Rica, responds to a series of social, cultural and historical conditions, framed within a patriarchal scheme in which attitudes and roles of masculinity and femininity predominate that favor that men have a greater exposure to risk of a road accident and suffering fatal or serious injuries than women, the result of a road system configured from the symbolism imposed by a misunderstood masculinity. The article aims to be an initial input to generate a wider and broader discussion about the impact of social roles associated with the condition of being a man or woman on road safety.